Transcriptomic analysis reinforces the implication of spatacsin in neuroinflammation and neurodevelopment - Liriopé Toupenet Marchesi; Daniel Stockholm; Typhaine Esteves; Marion Leblanc; Nicolas Auger; Julien Branchu; Khalid Hamid El Hachimi; Giovanni Stevanin (Scientific Reports, 2025)
Abstract Hereditary spastic paraplegia (HSP) encompasses a group of rare genetic diseases primarily affecting motor neurons. Among these, spastic paraplegia type 11 (SPG11) represents a complex form of HSP caused by deleterious variants in the SPG11 gene, which encodes the spatacsin protein. Previous studies have described several potential roles for spatacsin, including its involvement in lysosome and autophagy mechanisms, neuronal and neurites development or mitochondria function. Despite these findings, the precise function of the spatacsin protein remains elusive. To elucidate its function, we conducted an extensive RNA sequencing (RNAseq) experiment and transcriptomic analysis in three distinct neural structures (cerebellum, cortex and hippocampus) and at three different ages (6 weeks, 4 months and 8 months) in both wild type and Spg11 −/− mice. Our functional analysis of differentially expressed genes (DEGs) and Gene Set Enrichment Analysis (GSEA) revealed dysregulation in pathways related to inflammation, RNA metabolism and neuronal and neurite development, factors frequently implicated in neurodegenerative disorders. Notably, we also observed early deregulation in cellular pathways related to cell proliferation. Our results represent a significant step towards a better understanding of the functions of spatacsin in the cell and the underlying cellular mechanisms disrupted by its absence.